Intelligent high -power commutation equipment monitoring and control system - ZHOU PENG; TANG LUPING; LIANG DING (2018)
The utility model provides an intelligent high -power commutation equipment monitoring and control system, it includes remote monitoring device and high -power commutation equipment control system, high -power commutation equipment control system includes power module, DSP control module, CPLD drive module, data exchange module and synchronous detection module, wherein: DSP control module pass through data exchange module with CPLD drive module connects for carry out data interchange with CPLD drive module, and realize commutation equipment control system's communication, CPLD drive module with DSP control module, data exchange module and synchronous detection module are connected for carry out data interchange with DSP control module, and the sampling of commutation equipment control system's synchronization signal. Intelligent high -power commutation equipment monitoring and control system, adopt DSP+CPLD's framework, improve commutation equipment control system's stability and reliability. 本实用新型提出了种智能化大功率整